Screening of Physical and Emotional Child Abuse Risk and Protective Factors in a Group of High School Students - İnanıcı, Sinem Yıldız; Akdeniz, Esra; İnanıcı, Mehmet Akif (The Bulletin of Legal Medicine, 2020)
Objectives: Child abuse is a multidimensional phenomenon so planning prevention strategies, risk/protective factors should be obtained in a multilayered manner with regard to the individual, family, school, environment and policies. It is aimed to describe these factors among high school studentsMaterials and Methods: The participants’ mean age is 15.69 (Sd = .96) and 53.4% (n = 353) of them are female. The Rathus assertiveness inventory and the questionnaire included variables related to demographics, school and neighborhood, risky behaviors, family relationships/lifestyle, risky thinking styles, abuse experience in the immediate environment.Findings: 95.5% of the students (n = 631) live with their families and perceived economic status is moderate/below (51.1%, n = 337). 59 (9.6%) mothers and 104 (16.2%) fathers were university graduates. 397 (60.1%) participants come to the school by public transport and 39.5% (n = 261) has no-one to accompany. Having a violent school-mate rate is 40.7% (n = 269). Assertiveness did not differ by gender and class. Families’ child rearing practices are harder for the upper-class boys than for the girls, the boys find their families expectations too much and feel less appreciated. 284 (43%) participants had 3 or more children who abuse emotionally (n=284, 43%) and physically (n=135, 20.4%).Conclusion: Class and gender may affect substance use, truancy, neighborhood safety, school violence victimization. When abuse cannot be questioned directly, it can be guiding to examine whether students escape from school, whether there are close violent friends and whether they feel friends’ support.
Keywords: decision tree; neglect; ecological theory; prevention